2006
DOI: 10.1002/sia.2146
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between electrochemical reactivity and surface chemistry of amorphous carbon nitride films

Abstract: Amorphous carbon nitride (a-CN x ) films prepared by RF magnetron sputtering technique display a moderate electrochemical reactivity. However, after electrochemical activation by a cathodic pretreatment in acidic solution, they exhibit a quasimetallic behavior. This behavior has been notably assessed by scanning electrochemical microscopy (SECM). The approach curves show that the a-CN x electrode surfaces are made of active and inactive domains. These surfaces have also been characterized by atomic force micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…[1][2][3][4][5][6] The interest in carbon nitride has been renewed due to its potential as an electronic thin film for both cold cathode displays 7 and electrode materials in electrochemical studies of water treatment. 8 Electronic properties have been reported for both hydrogenated and nonhydrogenated amorphous carbon nitride. In particular, it is found that nitrogen incorporation has a beneficial effect on electric field emission at low microscopically applied fields by reducing the threshold electric field.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The interest in carbon nitride has been renewed due to its potential as an electronic thin film for both cold cathode displays 7 and electrode materials in electrochemical studies of water treatment. 8 Electronic properties have been reported for both hydrogenated and nonhydrogenated amorphous carbon nitride. In particular, it is found that nitrogen incorporation has a beneficial effect on electric field emission at low microscopically applied fields by reducing the threshold electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, on the only basis of our results and recent published work [41], the relationship between the electrochemical reactivity of amorphous carbon nitride and its structure still remains to be not well understood. In short, the electrochemical reactivity is often linked to several factors, especially the chemical groups created at the surface by introducing some functionalities as carbon-nitrogen or carbon-oxygen.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, the influence of a high fraction of edge plane on sp 2 carbon material on the electrochemical and electrical properties has to be considered. It is well known that in many cases the electrochemical pre-treatment could remarkably increase the reversibility of the charge transfer process as recently discussed by Cachet et al [41]. The authors correlated the electrochemical reactivity to the chemical surface composition of CN x materials and suggested that the sp 3 bonds could act as insulating sites.…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, applications in electroanalysis for heavy metals detection by stripping voltammetry [20][21][22][23] or biological analyte detection [24], in catalysis [25,26], for anti-corrosion coatings [27][28][29], humidity sensing [30], elaboration of a-CN x (or a-C)/metal composite materials [31][32] or new p-n junctions [33][34] A c c e p t e d M a n u s c r i p t 3 have been proposed. Moreover, these materials possess a very smooth surface, as shown from AFM images on a-CN x films when deposited by cathodic sputtering on doped silicon [35].…”
Section: Introductionmentioning
confidence: 96%